Comparison of three different chemotherapy regimens for concomitant chemoradiotherapy in locally advanced non-small cell lung cancer - YUMUK, PERRAN FULDEN (SPRINGER JAPAN KK, 2020)
Purpose The optimal chemotherapy regimen for concurrent chemoradiation in locally advanced non-small cell lung cancer (NSCLC) remains unclear. Cisplatin-etoposide regimen related toxicity is high, weekly regimens have been investigating. We aimed to compare the efficacy and safety of different concurrent chemotherapy regimens in the context. Methods A total of 225 patients with locally advanced, unresectable stage III NSCLC were included. Patients who were treated with weekly docetaxel-platin (DP), paclitaxel-platin (PP) and standard dose etoposide-platin (EP) chemotherapy regimens were selected and divided into groups for the comparison of toxicity, response rate, progression free survival (PFS), and overall survival (OS) times. Results There was a statistically significant difference between overall response rate of each treatment groups (DP: 96.1%, PP: 94% and EP: 76.7%,p < 0.001). The median PFS time of patients who were treated with DP, PP and EP was 16, 15 and 13.3 months, respectively (p = 0.435). The median OS time of patients treated with DP, PP and EP was 19.2, 29.7 and 28.3 months, respectively (p < 0.001). The rates of adverse events such as nausea, vomiting, neuropathy and anaphylaxis was similar. Grade 1-2 mucositis or esophagitis, anemia, pneumonitis were significantly higher in PP group than other groups. However, hematologic toxicities were higher in the EP group than other groups. Conclusions Compared to the weekly chemotherapy regimens with the standard dose, our study demonstrated similar PFS, but a prolonged OS with the EP regimen. The clinical response rate of weekly regimens was better than the full-dose regimen. Adverse events and toxicity rates were different and depended on the type of chemotherapy regimen used.
Keywords: Concomitant chemoradiotherapy; Non-small cell lung cancer; Locally advanced; Docetaxel; Paclitaxel; Etoposide; RANDOMIZED PHASE-II; CONSOLIDATION CHEMOTHERAPY; CONCURRENT CHEMORADIATION; THORACIC RADIOTHERAPY; CISPLATIN; PACLITAXEL; DOCETAXEL; TRIAL; CARBOPLATIN; ETOPOSIDE